Combined With Rose Aromatherapy And Progressive Muscle Relaxation Intervention To Maintain Stability Of Blood Pressure And Pain In Hypertensive Patients - Sakinah, Sri; Hasanuddin, Indirwan; Syamsu, Muh. Nur (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2025)
Background: The increase in hypertension cases is leading to an increase in premature deaths worldwide. Hypertension is a condition in which blood pressure increases due to a continuous increase in blood vessels. Globally, the prevalence of hypertension is as many as 1.13 billion people suffering from hypertension; Where 1 in 4 men and 1 in 5 women are at risk of developing hypertension. (WHO, 2023).Purpose: To determine the impact of the administration of rose aromatherapy and Progressive Muscle Relaxation on the reduction of hypertension in the working area of the Sabbangparu Health Center.Methods: This study uses a descriptive method in the form of a case study using a nursing process approach starting from assessment, diagnosis, planning, nursing actions, and evaluation of nursing results.Results: That with the administration of rose aromatherapy and progressive muscle relaxation can lower blood pressure and relieve pain.Conclusion: The intervention was given 1x/day in the afternoon at 16:30 WITA for 15 minutes which was carried out for 3 consecutive days. After 3 days of intervention, there was an improvement in blood pressure and pain reduction in hypertensive patients.